Development of E-Learning Flipped Classroom Model to Improve Learning Outcomes in the Natural and Social Sciences - Muhammad Khairil Asrori; Deni Hardianto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a flipped classroom e-learning model based on Moodle to improve learning outcomes in the Natural and Social Sciences (IPAS) subject for Grade X students at SMK N 1 Praya. The research employed the ADDIE development model, involving stages of analysis (student needs and learning barriers), design (LMS structure, blended strategies), development (digital content, expert validation), implementation (trial in class X Hospitality), and evaluation (formative-summative assessment). The model features pre-class videos, interactive quizzes, e-modules, and online assignments integrated into Moodle. Feasibility was assessed by media, material, and model experts using Likert-scale instruments, scoring 4.0 (feasible) and 4.7 (very feasible). Practicality was evaluated through teacher responses, scoring 4.85 (very practical). Effectiveness was measured via pretest and posttest using the N-Gain formula, showing an average gain of 0.59 (moderate improvement). The model was trialed with 34 students, considering the school's characteristics (vocational focus, limited practice time, and low student engagement). Results indicate that the flipped classroom e-learning model is feasible, practical, and effective in enhancing student outcomes in vocational science learning.